Islamic Education in the Context of Globalization: Facing the Challenges of Secularism and Materialism - Saepudin, Aep (International Journal of Science and Society, 2022)
Islamic education in the era of globalization faces various challenges, especially from the increasingly strong influence of secularism and materialism. Globalization brings major changes in social, economic, and cultural aspects, which affect the way the younger generation views religion and life. Islamic education needs to adapt to the demands of the times without sacrificing the spiritual values ​​that are its foundation. This study aims to identify strategies for strengthening Islamic education in facing the challenges of globalization, secularism, and materialism. This study uses a qualitative approach, by collecting data from various relevant research results and studies. After the data is collected, the analysis process is carried out in-depth to find relevant and significant findings. The results of this study indicate that Islamic education must integrate spiritual values ​​with modern sciences to remain relevant in the era of globalization. The main challenge is to maintain traditional values ​​while following developments in global science and technology. Islamic education also needs to respond to the influence of secularism with strategies that integrate religion in all aspects of life, not just in the formal curriculum. The materialism that prioritizes worldly success needs to be balanced with the instillation of spiritual awareness and social responsibility. Adaptive and innovative strategies for strengthening Islamic education are required to face the influence of globalization while maintaining the identity and moral values ​​taught in Islam.